Hubungan Antara Pendidikan Kesehatan Teknik Menyusui Dengan Praktik Menyusui Ibu Nifas Di Desa Tanggeran Kecamatan Tonjong Kabupaten Brebes 2022 - Tati Karyawati; Siti Fatimah; Maulia Arfin Hani; Melizza Shofarina (Pusat riset dan Inovasi Nasional, 2022)
Nursing mothers usually fail to breastfeed or stop breastfeeding early because they do not know breastfeeding techniques. This can cause interference in the breastfeeding process. To achieve successful breastfeeding requires knowledge of correct breastfeeding techniques by providing information in the form of breastfeeding techniques through health education. The aim of the research is to determine the relationship between health education on how to breastfeed and the breastfeeding practices of postpartum mothers in Tanggeran Village, Tonjong District, Brebes Regency in 2022. This type of research uses descriptive methods with a cross-sectional approach with a total of 25 postpartum mothers in Tanggeran Village, Tonjong District, Brebes Regency in 2022. Results: research using the chi Square statistical test, obtained a p-value = 0.003, which means it is smaller than the value α = 0.05. (OR 16.5; 95%; CI 2.246-121.228). there is a relationship between health education on how to breastfeed and the breastfeeding practices of postpartum mothers in Tanggeran Village, Tonjong District, Brebes Regency in 2022.